Analysis of Commander Authorities to Punish subordinate in the Implementation of Disciplinary Legal Sanctions Against Soldiers Who Violate Discipline Regulations - Andrew Gerard Batara; R.R. Eko Widy Astuty Sumanto; Busatto Marilia; Tostes Geraldo; Costa Rita (Yayasan Adra Karima Hubbi, 2023)
Background. The application of legal sanctions for soldier discipline within the Indonesian Army is an attempt to minimize the existence of violations that occur among Indonesian Army soldiers. In this case, every commander has the authority to take disciplinary action against every subordinate who violates the law on soldier discipline and immediately reports it to the Ankum concerned. Purpose. This study aims to determine the function of Ankum's (Atasan yang berhak menghukum – commander with the right to punish) authority in the application of disciplinary sanctions for TNI soldiers. To find out the effectiveness of the application of disciplinary legal sanctions to prevent the recurrence of disciplinary law violations of TNI soldiers. Method. This study uses normative research methods, by collecting primary data in the form of interviews with Ankum. And secondary data in the form of laws, books, journals, and related scientific articles. Results. The results of this study, namely Ankum's authority in applying disciplinary sanctions to TNI soldiers by imposing penalties on TNI soldiers who commit disciplinary violations and the behavior of soldier disciplinary violations are influenced by 2 (two) kinds of factors, namely internal and external factors. Ankum must implement effective leadership. Conclusion. The application of legal sanctions for soldier discipline within the Indonesian Army is an attempt to minimize the existence of violations that occur among Indonesian Army Force. In this case, every commander has the authority to take disciplinary action against every subordinate who violates the law on soldier discipline and immediately reports it to the Ankum concerned..